2011
DOI: 10.1007/978-3-642-24178-9_22
|View full text |Cite
|
Sign up to set email alerts
|

CoCo: Coding-Based Covert Timing Channels for Network Flows

Abstract: Abstract. In this paper, we propose CoCo, a novel framework for establishing covert timing channels. The CoCo covert channel modulates the covert message in the inter-packet delays of the network flows, while a coding algorithm is used to ensure the robustness of the covert message to different perturbations. The CoCo covert channel is adjustable: by adjusting certain parameters one can trade off different features of the covert channel, i.e., robustness, rate, and undetectability. By simulating the CoCo cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…inter-packet delays. In [13], the authors present the CoCo covert channel which modulates the covert message in the inter-packet delays of the network flows, with a coding algorithm that is used to ensure the robustness of the covert message to different perturbations.…”
Section: Related Workmentioning
confidence: 99%
“…inter-packet delays. In [13], the authors present the CoCo covert channel which modulates the covert message in the inter-packet delays of the network flows, with a coding algorithm that is used to ensure the robustness of the covert message to different perturbations.…”
Section: Related Workmentioning
confidence: 99%
“…Network covert channels have been demonstrated that are provably undetectable from normal "overt" traffic [25]. Such channels are comprised of a sender process exfiltrating secret data through inter-packet timing or packet sizes, for example.…”
Section: Formal Model For Covert Channelsmentioning
confidence: 99%
“…The goal of a covert channel is to conceal the very existence of a covert message by communicating it through legitimate channels [16].…”
Section: Related Workmentioning
confidence: 99%
“…Another difference is that with Jitterbug the receiver must be able to intercept network traffic, while our approach can be used by any unprivileged user. CoCo, introduced in [16] by Houmansadr et al, is a framework for establishing covert channels via inter-packet delays. The sender generates a traffic flow directed to the receiver, then manipulates the flow according to the covert message and a key, shared between the two parties.…”
Section: Related Workmentioning
confidence: 99%